The role of pyroptosis in cognitive impairment - Yang, Xin; Tang, Zhe (Frontiers in Neuroscience, 2023)
Cognitive impairment is a major global disease, manifests as a decline in cognitive functioning and endangers the health of the population worldwide. The incidence of cognitive impairment has increased rapidly with an increasingly aging population. Although the mechanisms of cognitive impairment have partly been elucidated with the development of molecular biological technology, treatment methods are very limited. As a unique form of programmed cell death, pyroptosis is highly pro-inflammatory and is closely associated with the incidence and progression of cognitive impairment. In this review, we discuss the molecular mechanisms of pyroptosis briefly and the research progress on the relationship between pyroptosis and cognitive impairment and its potential therapeutic values, to provide a reference for research in the field of cognitive impairment.